COMPARATIVE PERFORMANCE OF POLY VOLTINE XBIVOLTINE HYBRIDS OF SEX-LIMITED COCOON COLOUR BREEDS OF SILKWORM, BOMBYX MORI L. UNDER DIFFERENT ENVIRONMENTAL CONDITIONS - JOGE, P. G.; BASAVARAJA, H. K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2007)
In the present study an attempt has been made to evaluate the performance of the bivoltine sexlimited cocoon colour breeds with normal breeds and their polyvoltine X bivoltine hybrids under three different temperature and humidity conditions (25+1°C (65t5% RH), 3 lit1°C (50.5% RH) and 36tl°C (85+5% RH). By utilizing four bivoltine breeds viz. CSR2 normal, CSR2(SL) sex-limited for cocoon coloro, NB4D2 and CSR8(SL) sex-limited for cocoon color and 6 polyvoltine breeds viz. PM, Nistari, BL67, MY1, RD1, and PV1, 24 poly Voltine X bivoltine hybrids were prepared and studied. Significant differences were noticed for majority of the characters in bivoltine and polyvoltine breeds and their hybrids at different environmental conditions. The results of this study indicate that the performance of sex-limited cocoon colour bivoltine breed CSR2(SL) was marginally better than the normal bivoltine breed, CSR2 and also indicate that hybrids of sex limited breed CSR2(SL) with all polyvoltine breeds performed better than other breeds at adverse conditions. Therefore, it is concluded that sex-limited cocoon colour breed CSR2(SL) can be used as male component for preparation of polyvoltine x bivoltine hybrids throughout the year. Key words : , , , ,.